Pt-Co and Pt-Ni Catalysts of Low Metal Content for H2 Production by Reforming of Oxygenated Hydrocarbons and Comparison with Reported Pt-Based Catalysts. (11th July 2018) - Dosso, Liza A.; Vera, Carlos R.; Grau, Javier M.
Abstract : New catalysts of Pt, PtNi, PtCo, and NiCo supported on Al2 O3 were developed for producing hydrogen by aqueous phase reforming (APR) of oxygenated hydrocarbons. The urea matrix combustion technique was used for loading the metal on the support in order to improve several aspects: increase both the metal-support interaction and the metal dispersion and decrease the metal load. The catalysts were characterized by MS/ICP, N2 adsorption, XRD, TPR, CO chemisorption, and the test of cyclohexane dehydrogenation (CHD). The APR of a solution of 10% mass ethylene glycol (EG), performed in a tubular fixed bed reactor at 498 K, 22 bar, WHSV = 2.3 h −1, was used as the main reaction test. After 10 h on-stream, the catalysts prepared by UMC had better hydrogen yield and catalytic stability than common catalysts prepared by IWI. The UMC/IWI H2 yield ratio was 23.5/15.2 for Pt, 24.0/17.0 for PtCo, 26.6/21.0 for PtNi, and 8.0/3.9 for NiCo. Ni or Co addition to Pt increased the carbon conversion while keeping the H2 turnover high. Cobalt also improves stability. Reports of several authors were revised for a comparison. The analysis indicated that the developed catalysts are a viable and cheaper alternative for H2 production from a renewable resource.